Improving Students Skills in Assembling Electronic Circuits Through an Experiment-Based Problem-Solving Learning Model - T. Aulia Rizky (PTE FTK UIN Ar-Raniry, 2026)
Vocational education is the main key to improving student competencies that are in accordance with the needs of the workplace. However, learning activities in the subject of Basic Electronics require effective learning strategies that engage students in solving real-world problems. Therefore, this study aims to improve student learning outcomes through the implementation of a problem-solving learning model in the subject of Basic Electronics at SMK Negeri 5 Banda Aceh. This study used a Classroom Action Research design consisting of two cycles. The research participants were 15 students of grade XI with a test sheet instrument, which was used to measure student learning outcomes after the implementation of the treatment in learning. The results showed that there was an increase in student learning outcomes with the percentage of students achieving the Minimum Mastery Criteria (KKM) with an average score of 79% in Cycle I and increasing to 87.6% in Cycle II. The results of the study showed a significant change in student performance. This indicates that the application of the problem-solving learning model can be an effective alternative to increase active student participation and encourage the achievement of better learning outcomes in learning Basic Electronics and other productive subjects